SINODE DAN PENOLAKAN PRIVATISASI PANTAI PEDE - Inosentius Mansur (STIPAS St. Sirilus Ruteng, 2016)
One of important points of Synod III dioses of Ruteng is to refuse the privatization of Pede Beach by enterpreneur. It's the reasonable decision.Pede Beach is the only one of public space that so far could be accessed by public freely. The government of NTT province that has the property of rights of Pede Beach enstruted the third party to manage Pede Beach. In this case, PT Sarana Investama Menggabar (SIM) of Setya Novanto is the party that will get the big benefit.Itseems, Memoranduum of Understanding (MoU)between NTT province and PT SIM has dealt the 25 years ofcontract byPT SIM in managing Pede Beach. Of course, it will increse the capitalization of public space on the coastal area of Labuan Bajo. It means, in just a little while the indegenous of Manggarai Barat will be